(untitled) (Veterinary Science, 2017)
There are multiple risk factors connected to children’s environmental health among which in children under five years old the main causes of death are diarrhea, air contamination, pathologies, non-intentional physical trauma, vectorial and acute respiratory diseases, chemical and physical risks. Pet presence is intrinsically related to some of them. The objective of this work was to describe the environmental situation and prevalent diseases in children from the Veterinary Public Health point of view in the programmatic area of the Brown Health Center. A descriptive study was done between June and September 2011. Questionnaires were handed out from the public initial level establishments in the area and professionals, that work in the Center above mentioned, were interviewed. We asked about social demographic variables and the presence of possible risk factors for children’s environmental health. From the 83 answers received from the responsible people of their homes, we obtained the following results: 89.15% of the answers came from wom en. More than 50% of the adult population is in school or has an elementary school level; occupational level is precarious in 56.63% of the population; there is overcrowding in 26.5% of the houses; there is 59.04% of smokers; in 74.4% of the homes interviewed they live with different pets from which 40.91% pay visits to the Veterinary Doctor. Plague presence in the area gave the following results: rodents: 21.70%; mosquitoes: 44.57%; bats: 15.66%; others: 18.07%. Neighborhood observations, interviews to professionals and teachers widened the information obtained and verified the poor health environment to which children are exposed. Implementation of diverse strategies from an interdisciplinary point of view, with community participation, are required.